學校創新經營對家長選校意願影響之研究─以服務品質與學校形象為中介變項 Impacts of School Innovation Management on School Selecting Intentions: Service Quality and School Image as Mediators - 劉祥熹 Hsiang-Hsi Liu; 陳玉娟 Yu-Chuan Chen; 鄭筱慧 Hsiao-Hui Cheng (National Taiwan Normal University, 2016)
本研究目的在剖析以服務品質與學校形象為中介變項下，學校創新經營對家長選校意願的影響狀況，進而提出公立國民中學經營策略上之見解與作法，以提供公立國民中學於創新經營、服務品質與學校形象方面之策略建議。為達成研究目的，本研究利用問卷調查蒐集實證資料，並進行結構方程模式分析。研究結果發現，學校創新經營對服務品質與學校形象皆呈現正面的影響效果、服務品質與學校形象對選校意願呈現正面的影響效果、服務品質對學校形象呈現正面的影響效果，服務品質與學校形象於本研究模式中扮演重要的中介性角色；最後，研究者依本研究結果提出相關建議。 This study tries to explore the mediatory roles of service quality and school image in the relationships between school innovation management and school-selecting intentions for public junior high schools. A survey was conducted to collect data, which were then analyzed using the structural equation model. The empirical results reveal that the school innovation management has a positive effect on service quality and school image, and that both service quality and school image positively affect school-selecting intentions. In addition, service quality has a positive effect on school image. Furthermore, both service quality and school image play effective and positive intermediary roles in the adopted research model. Suggestions are also provided on innovation management in public junior high schools in this study.